Instructional Needs Analysis and Cultural Values in Online Learning - Hanoum, Nadia; Silvana, Hana (International Journal of Education, 2019)
From a cultural perspective, the nature of online learning is related to learners’ high individualism and low power distance between learners and instructor, which is in contradictory with Indonesian cultural values of high collectivism and high power distance. This study aimed to analyze the cultural values of Indonesian learners, identify the instructional needs that were compatible with the learning culture, and design an instructional design framework which is compatible with the learning culture of Indonesian students in general so that the learning process can be maximized. This study employed quantitative descriptive method and a questionnaire was used as the instrument to gather data from a sample taken purposively, that is students who took online learning via Integrated Online Learning System (SPOT) learning management system. The results suggested that Indonesian students exhibited high power distance, low tolerance for uncertainty and were culturally more collectivist and feminine. These cultural values have implications on the process of online learning in three different areas, namely assessment, instruction, and communication. Thus, a framework of learning strategies has been proposed to overcome the problems posed by the learning culture of Indonesian students so that the online learning can be more effective.